Energy management of PV wind based microgrid with hybrid energy storage systems - Suganthi Neelagiri; Pasumarthi Usha (Institute of Advanced Engineering and Science, 2022)
Power demand all around the world is increasing day by day and conventional energy sources are getting depleted. In order to meet the power demand and to reduce the carbon emission caused by the conventional energy sources, alternate renewable energy sources are important. wind and solar are two reliable energy sources among the various renewable energy sources. In this proposed paper wind and photovoltaic (PV) energy-based direct current (DC) microgrid is proposed with super capacitor and battery hybrid energy storage systems. Constant DC link voltage is the replication of energy balance in DC microgrid. The main goal of the proposed microgrid energy management algorithm is to maintain the constant DC link voltage irrespective of the intermittent nature of the renewable energy sources, load variations and under fault conditions. Energy management system is designed such that battery energy storage system handles the average power requirements and super capacitor handles the transient power requirements caused by the load, renewable energy variation and also caused due to fault conditions. The proposed system improves battery life along with effective DC link voltage regulation. The proposed control algorithm of energy management is compared with conventional energy management system in MATLAB/Simulink and presented for various studies.